Comparing the quality of passively-scattered proton and photon tomotherapy plans for brain and head and neck disease sites. (16th February 2015) - Kainz, Kristofer; Firat, Selim; Wilson, J Frank; Schultz, Christopher; Siker, Malika; Wang, Andrew; Olson, Dan; Allen Li, X
Abstract: We compare the quality of photon IMRT (helical tomotherapy) with classic proton plans for brain, head and neck tumors, in terms of target dose uniformity and conformity along with organ-at-risk (OAR) sparing. Plans were created for twelve target volumes among eight cases. All patients were originally planned and treated using helical tomotherapy. Proton plans were generated using a passively-scattered beam model with a maximum range of 32 g cm −2 (225 MeV), range modulation in 0.5 g cm −2 increments and range compensators with 4.8 mm milling tool diameters. All proton plans were limited to two to four beams. Plan quality was compared using uniformity index (UI), conformation number (CN) and a EUD-based plan quality index (fEUD). For 11 of the 12 targets, UI was improved for the proton plan; on average, UI was 1.05 for protons versus 1.08 for tomotherapy. For 7 of the 12 targets, the tomotherapy plan exhibited more favorable CN. For proximal OARs, the improved dose conformity to the target volume from tomotherapy led to a lower maximum dose. For distal OARs, the maximum dose was much lower for proton plans. For 6 of the 8 cases, near-total avoidance for distal OARs provided by protons leads to improved fEUD. However, if distal OARs are excluded in the fEUD calculation, the proton plans exhibit better fEUD in only 3 of the 8 cases. The distal OAR sparing and target dose uniformity are generally better with passive-scatter proton planning than with photon tomotherapy; proton therapy may be preferred if the clinician deems those attributes critical. However, tomotherapy may serve equally as well as protons for cases where superior target dose conformity from tomotherapy leads to plan quality nearly identical to or better than protons and for cases where distal OAR sparing is not concerning.